Technological and sensory analysis of beef burger replacing NaCl with KCl and flavor enhancer - Silva, Juliana Resende Gonçalves; Pires, Ana Paula de Souza; Oliveira, Dairo Cabral de; Silva, Vanessa Riani Olmi; Benevenuto Junior, Augusto Aloísio; Franco, Frederico Souzalima Caldoncelli (Acta Scientiarum. Technology, 2019)
High sodium consumption may increase the risk of hypertension. ANVISA has proposed reducing sodium levels in food, but this may reduce consumer acceptance. This study investigated the technological and sensory profile of samples of beef burger replacing NaCl with KCl added flavor enhancers, namely: CON (100% NaCl), F50 (50% NaCl and KCl + PuraQ®Arome NA4), and F60 (40% NaCl and 60% KCl + PuraQ®Arome NA4). Physicochemical, technological, microbiological and sensory parameters of the formulations were evaluated. There was no difference between formulations in microbiological, physicochemical and technological parameters. For color analysis, F60 reduced to the coordinate a* and raised b* compared to the CON. In sensory analysis, F60 reduced the flavor attribute compared to the CON. PuraQ® minimized the salty perception of the F50, however, but did not avoid the residual flavor in the F60. The principal component analysis associated the attributes with the formulations as follows: succulent and ideal seasoning (CON), soft and without salt (F50), and salty and residual flavor (F60). It was concluded that the reduction of 50% of NaCl added enhancer was better accepted by consumers, being a promising strategy in reducing sodium in burgers.